2021
DOI: 10.7717/peerj.11596
|View full text |Cite
|
Sign up to set email alerts
|

2018 Survey of factors associated with antimicrobial drug use and stewardship practices in adult cows on conventional California dairies: immediate post-Senate Bill 27 impact

Abstract: Background Antimicrobial drugs (AMD) are critical for the treatment, control, and prevention of diseases in humans and food-animals. Good AMD stewardship practices and judicious use of AMD are beneficial to the preservation of animal and human health from antimicrobial resistance threat. This study reports on changes in AMD use and stewardship practices on California (CA) dairies, following the implementation of CA Senate Bill 27 (SB 27; codified as Food and Agricultural Code, FAC 14400–14408; here onward refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 35 publications
5
13
1
Order By: Relevance
“…Our results showed that dairy producers who reported tracking both milk and meat withdrawal intervals during AMD treatment or those who reported having a VCPR were more familiar with the FDA’s term “MIADs” than those who did not report. These findings agree with findings from the survey conducted the year SB 27 was implemented [ 15 ]. However, our survey showed that 34.2% of the dairy respondents were not familiar with or not sure how the FDA’s term “MIADs” related to their dairies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results showed that dairy producers who reported tracking both milk and meat withdrawal intervals during AMD treatment or those who reported having a VCPR were more familiar with the FDA’s term “MIADs” than those who did not report. These findings agree with findings from the survey conducted the year SB 27 was implemented [ 15 ]. However, our survey showed that 34.2% of the dairy respondents were not familiar with or not sure how the FDA’s term “MIADs” related to their dairies.…”
Section: Discussionsupporting
confidence: 91%
“…Our machine learning models also showed that the majority (84%) of the large dairy producers were classified as producers with “good to excellent” AMS knowledge compared with producers of small dairies. Similarly, the survey by Ekong et al [ 15 ] found that large dairies producers were more familiar with MIADs, reported a greater use of alternatives to AMD, and reported better animal health compared to small dairy producers after implementation of SB 27.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The objective of the survey was to characterize antimicrobial stewardship practices, AMD use, and health management of adult cows on CA dairies since the implementation of the VFD and SB 27. The associations between the management practices on conventional dairies and key antimicrobial stewardship and health outcomes are described elsewhere (Ekong et al, 2021).…”
Section: Introductionmentioning
confidence: 99%